KOMUNITAS MINANGKABAU DI SURABAYA - Mila; Miftahus Syifa Bahrul Ulumiyah (Qurthuba: The Journal of History and Islamic Civilization, 2023)
Abstract: This article seeks to understand the Mingkabau Community in Surabaya, focusing on discussing marriage procedures. In the scope of the discussion, there is a side of dynamism or a different form of change in the Minangkabau traditional marriage procedure from the place of birth to the customs in the city of Surabaya. This study uses two approaches, namely emic and etic and applies ethnography as the method. The analytical tool uses the theory of Continuity and Change by John Obert Voll. The results of this search concluded that: 1) Minangkabau marriages in West Sumatra have various kinds of processions that have meaning to carry out marriages; 2) Minangkabau weddings in Surabaya have fewer processions than those in West Sumatra; 3) there is a combination with the Minangkabau marriage procedures with local customs. Keywords: Minangkabau community, marriage procedures, change, Surabaya